Regulating Manufacturing FDI: Local Labor Market Responses to a Protectionist Policy in Indonesia - Esther Gehrke; Robert Genthner; Krisztina Kis-Katos (Institute of Labor Economics (IZA), 2024)
We analyze the effect of rising protectionism towards foreign direct investment (FDI) on domestic employment, exploiting revisions in Indonesia's highly-granular negative investment list, and spatial variation in the exposure of the manufacturing sector to these investment restrictions. Rising FDI restrictions caused employment gains at the local level, explaining about one-tenth of the aggregate employment increases observed between 2006 and 2016 in Indonesia. These employment gains went along with a reorganization of the local production structure, and new firm entries in the manufacturing sector that are concentrated among micro and small enterprises. While our results are consistent with an increase in the labor-to-capital ratio and reduced productivity among regulated firms (which allowed smaller and less productive firms to enter the market), we also document that at least half of the employment gains are driven by spillover-effects along the local value chain and into the service sector.
Keywords: F16; F21; F23; J23; J31; L51; 330; FDI regulation; Indonesia; local labor markets